The Power of Tax Relief: How Fiscal Incentives Shape the Creative Industries in Indonesia - Hidayah, Nurul; Pangestika, Ratna Rosita; Purnamasari, Niken (JAFFA, 2026)
This study examines the impact of fiscal incentives, particularly tax relief, on the performance of firms in Indonesia’s creative industries. While tax incentives are widely used to stimulate investment and innovation, their effectiveness in high-uncertainty, intangible-capital sectors such as creative industries is underexplored. In addition, this study also examines the moderating role of policy design, digital maturity, and export orientation. Using institutional theory as a framework, the study applies a fixed-effects panel regression model to 600 firm-year observations from 100 creative firms across 12 Indonesian provinces between 2019 and 2024. The findings reveal that tax relief significantly enhances firm performance, particularly in employment growth, capital investment, and RD. However, the benefits are stronger for firms operating under well-designed policy frameworks, with higher digital maturity or export orientation. This indicates that institutional and firm-specific factors critically shape the effectiveness of fiscal incentives. This study contributes original insights by linking policy design with firm outcomes, offering strategic recommendations for aligning fiscal tools with the digital and innovation-driven nature of the creative economy.